2013
DOI: 10.1007/s10750-013-1741-0
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Effects of mute swans on wetlands: a synthesis

Abstract: Due to an unfortunate turn of events, the first-and surnames of all authors were transposed in the original publication. The correct representation of the authors and their affiliations are listed above and below and should be treated as definitive by the reader.The online version of the original article can be found under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Our study shows that bird density is important to take into account to obtain the most accurate prediction of the CNL. Although we show that the CNL of a lake is negatively affected by grazing birds, controlling their abundance (see for instance discussion on management of mute swans (Wood et al, 2013;Gayet et al, 2014) would not bring a sustainable solution: the impact of birds is highest in the domain where the resilience of the clearwater state is already low because of high nutrient loading. While bird management may potentially be part of a set of management measures that can be applied to increase the resilience of the clear-water state, the vulnerability to regime change during eutrophication is primarily a function of the external nutrient loading (Scheffer et al, 1993).…”
Section: Discussionmentioning
confidence: 88%
“…Our study shows that bird density is important to take into account to obtain the most accurate prediction of the CNL. Although we show that the CNL of a lake is negatively affected by grazing birds, controlling their abundance (see for instance discussion on management of mute swans (Wood et al, 2013;Gayet et al, 2014) would not bring a sustainable solution: the impact of birds is highest in the domain where the resilience of the clearwater state is already low because of high nutrient loading. While bird management may potentially be part of a set of management measures that can be applied to increase the resilience of the clear-water state, the vulnerability to regime change during eutrophication is primarily a function of the external nutrient loading (Scheffer et al, 1993).…”
Section: Discussionmentioning
confidence: 88%
“…Many fish species are predators to macroinvertebrates, while those species introduced to serve anthropogenic purposes (e.g., mosquitofish) can cause substantial injuries to large numbers of larval amphibians in a wetland (Shulse & Semlitsch, 2013). Other introduced species like crayfish or mute swans are likely to impact either native species (e.g., amphibians) and habitat structure (e.g., macrophyte beds; Gayet et al, 2013), but the extent of adverse impacts generated by these species appears to be density-dependent.…”
Section: Highlightsmentioning
confidence: 99%
“…Our results have more general implications when it comes to the presumed impact of large and increasing herbivorous birds such as swans on other waterfowl species (Conover and Kania 1994;Pöysä and Sorjonen 2000;Gayet et al 2014Gayet et al , 2016, and whether these species thus could be considered 'invasive' sensu Valéry et al (2008Valéry et al ( , 2009, i.e. irrespective of whether they are native or not (see also Carey et al 2012;Gayet et al 2014). Specifically, it has been proposed that increasing swan populations in general have negative impact on abundance of other waterfowl species.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Gayet et al (2011b) did not find any negative impact of Mute Swan (Cygnus olor) pair presence on the occurrence of other waterbirds on fishponds in eastern France. Gayet et al (2014) also concluded that Mute Swan population increase cannot be considered as a biological invasion in Europe. Nor did find support for the idea that swans in general are more aggressive than other groups of waterbirds.…”
Section: Discussionmentioning
confidence: 99%